From virtual to venomous: Study of hate speech on Facebook through the hashtags Jesuischaima and Justicepourchaima - MESSAOUDI Adil; MEDANE Hadjira (International Journal of Social Communication, 2023)
Our research is in the field of digital speech analysis. Through this study we try to study and analyze the hate speech spread through two Hashtags of support and solidarity (#Jesuischaima and #Justicepourchaima) launched on the social network Facebook, following the murder of a teenage girl named Chaïma SADOU. We tried to highlight the linguistic means used by Internet users to express their feelings of hatred. To do this, we have presented the different types of hate speech. Then, we analyzed the different linguistic manifestations of hate speech, namely subjectivemes, threatening acts, acts of condemnation as well as the various discursive strategies deployed.